1992
DOI: 10.17763/haer.62.4.kxt8x5u037g46687
|View full text |Cite
|
Sign up to set email alerts
|

Labels, Literacy, and Enabling Learning: Glenn's Story

Abstract: Too often, the school system regards students who do not learn quickly enough or in a conventional manner as "deficient," and labels them in ways that keep them from joining in a dynamic learning process. In this powerful account of what a creative and trusting relationship between teacher and student can accomplish, Colleen Fairbanks tells of a young man's determination to overcome his "learning disabilities"label and of the consequences the labeling process had on his school life. In so doing,her own story e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Schools and educational systems are the decisive factors that create, and are responsible for maintaining, favourable conditions for promoting labelling in relation to disability (Slee and Rigby, ). Fairbanks () acknowledges that schooling becomes an agent in impeding intellectual and social growth for the labelled student. Bak, Cooper, Dobroth and Siperstein () observed that placements of individuals in special education programmes can act as de facto labels.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schools and educational systems are the decisive factors that create, and are responsible for maintaining, favourable conditions for promoting labelling in relation to disability (Slee and Rigby, ). Fairbanks () acknowledges that schooling becomes an agent in impeding intellectual and social growth for the labelled student. Bak, Cooper, Dobroth and Siperstein () observed that placements of individuals in special education programmes can act as de facto labels.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Social construction of disability hinges on assigning labels of deviance and the construction of ‘other’. Fairbanks () highlights three major problematic aspects of the assignment of labels: (1) labels are negative in their depiction of deficits; (2) labels become the defining characteristic of the person, denying their complex whole; (3) the use of labels for identifying ‘special education needs’ fails to locate failure properly in the education system. Thus, from this perspective, labelling is believed to be detrimental to self‐esteem and self‐concept (McDermitt, ; Slee and Rigby, ; Osterholm et al ., ).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…First, the case study. There were some examples such as the works of Fairbanks (1992) and Brenzel (1980) in HER.…”
Section: Educational Research Focusing On Teaching Object: the Studenmentioning
confidence: 99%
“…This is especially true for Black males. The practice of mis/labeling often has lingering negative effects on Black males (Abidin et al, 1972; Fairbanks, 1992). One such impact is disproportionality.…”
mentioning
confidence: 99%